Functional Characterization of a Novel Oxidative Stress Protection Protein in the Pathogenic Yeast Candida glabrata - Usher, Jane; Chaudhari, Yogesh; Attah, Victoria; Ho, Hsueh-lui; Haynes, Ken (Frontiers in Genetics, 2020)
Candida species are important pathogens of humans and the fourth most commonly isolated pathogen from nosocomial blood stream infections. Although Candida albicans is the principle causative agent of invasive candidosis, the incidence of Candida glabrata infections has rapidly grown. The reason for this increase is not fully understood, but it is clear that the species has a higher innate tolerance to commonly administered azole antifungals, in addition to being highly tolerant to stresses especially oxidative stress. Taking the approach that using the model organism, S. cerevisiae, with its intrinsic sensitivity to oxidative stress, we hypothesized that by expressing mediators of stress resistance from C. glabrata in S. cerevisiae, it would result in induced resistance. To test this we transformed, en-masse, the Candida glabrata ORFeome library into S. cerevisiae. This resulted in 1,500 stress resistant colonies and the recovered plasmids of 118 ORFs. Sequencing of these plasmids revealed a total of 16 different C. glabrata ORFs. The recovery of genes encoding known stress protectant proteins such as GPD1, GPD2 and TRX3 was predicted and validated the integrity of the screen. Through this screen we identified a C. glabrata unique ORF that confers oxidative stress resistance. We set to characterise this gene herein, examining expression in oxidative stress sensitive strains, comet assays to measure DNA damage and synthetic genetic array analysis to identify genetic interaction maps in the presence and absence of oxidative stress.